The Role of Celebrity Endorsements in Breaking Advertising Clutter and reducing Advertising Avoidance on Social Media Networks - Mosa, Raafat Awad (International research journal of management, IT and social sciences, 2022)
In the light of the business environment dominated by marketing noise and advertisements that surround us from every angle, relying on the popularity of social networks has become insufficient to pass advertising messages into the minds of the customers. We live today amid a sea of advertising clutter that undermined the efforts of marketers in conveying their voices to target customers. Besides, technology has given customers greater opportunities to choose the appropriate way to deal with advertising messages, whether by ignoring or blocking them. Therefore, the study sought to reveal the extent of the existence of advertising clutter on social media networks and its relationship to advertising avoidance, and then determine the role that celebrity endorsement can contribute to breaking this clutter and reducing advertising avoidance. The study adopted the quantitative approach in measuring its variables by surveying a large sample of Iraqi social network users, which numbered (837) respondents. The study concluded that advertising clutter on social networks has reached unjustified and unwelcome levels. Moreover, the results confirmed that the celebrity endorsement strategy has a prominent role in penetrating clutter and reducing advertising avoidance.